Reduced-order thermomechanical modeling of multibody systems using floating frame of reference formulation. (September 2019) - Yamashita, Hiroki; Arora, Rohit; Kanazawa, Hiroyuki; Sugiyama, Hiroyuki
In this study, a reduced-order thermomechanical coupling model, which accounts for the inertia coupling of the thermoelastic deformation and the large reference body motion, is proposed using the floating frame of reference formulation for the transient thermomechanical analysis of constrained multibody systems. In this approach, the reduced-order heat equations are fully embedded in the final form of the equations of motion. Accordingly, the transient thermal response as well as the resulting thermoelastic behavior of constrained multibody system can be predicted within the general multibody dynamics computer algorithm. It is demonstrated that appropriate selection of the thermal interface coordinates is crucial for describing the thermal modes (i.e. temperature distribution) induced by external heat sources using the Craig–Bampton component mode synthesis approach generalized for thermomechanical systems. Furthermore, a systematic procedure for imposing prescribed surface temperature given, for example, from thermal-fluid dynamics simulations is proposed for the thermomechanical floating frame of reference formulation. Using several numerical examples, simulation capabilities of the thermomechanical floating frame of reference formulation model are demonstrated for multibody dynamics applications. Numerical results show good agreement with the nonlinear thermomechanical finite element solutions considering the large rotational motion with substantial reduction in the model dimensionality and computational time.